Bufalin-Loaded Multifunctional Photothermal Nanoparticles Inhibit the Anaerobic Glycolysis by Targeting SRC-3/HIF-1α Pathway for Improved Mild Photothermal Therapy in CRC - Shang J; Xia Q; Sun Y; Wang H; Chen J; Li Y; Gao F; Yin P; Yuan Z (International Journal of Nanomedicine, 2024)
Jing Shang,1,* Qi Xia,1,* Yuji Sun,2 Hongtao Wang,2 Jia Chen,1 Yue Li,1 Feng Gao,2 Peihao Yin,1,3,4 Zeting Yuan1– 4 1Interventional Cancer Institute of Chinese Integrative Medicine, Putuo Hospital, Shanghai University of Traditional Chinese Medicine, Shanghai, 200062, People’s Republic of China; 2Shanghai Frontiers Science Center of Optogenetic Techniques for Cell Metabolism, Shanghai Key Laboratory of New Drug Design, School of Pharmacy, East China University of Science and Technology, Shanghai, 200237, People’s Republic of China; 3Shanghai Putuo Central School of Clinical Medicine, Anhui Medical University, Shanghai, 200062, People’s Republic of China; 4The Fifth School of Clinical Medicine, Anhui Medical University, Hefei, 230032, People’s Republic of China*These authors contributed equally to this workCorrespondence: Zeting Yuan; Peihao Yin, Interventional Cancer Institute of Chinese Integrative Medicine, Putuo Hospital, Shanghai University of Traditional Chinese Medicine, Shanghai, 200062, People’s Republic of China, Email yuan340202@163.com; yinpeihao@shutcm.edu.cnPurpose: Compared with traditional photothermal therapy (PTT, > 50°C), mild PTT (≤ 45°C) is a promising strategy for tumor therapy with fewer adverse effects. Unfortunately, its anti-tumor efficacy is hampered by thermoresistance induced by overexpression of heat shock proteins (HSPs). In our previous study, we found bufalin (BU) is a glycolysis inhibitor that depletes HSPs, which is expected to overcome thermotolerance of tumor cells. In this study, BU-loaded multifunctional nanoparticles (NPs) were developed for enhancing the mild PTT of colorectal cancer (CRC).Methods: Fe3O4 NPs coated with the polydopamine (PDA) shell modified with polyethylene glycol (PEG) and cyclic arginine-glycyl-aspartic peptide (cRGD) for loading BU (Fe3O4@PDA-PEG-cRGD/BU NPs) were developed. The thermal variations in Fe3O4@PDA-PEG-cRGD/BU NPs solution under different conditions were measured. Glycolysis inhibition was evaluated by measuring the glucose uptake, extracellular lactate, and intracellular adenosine triphosphate (ATP) levels. The cellular cytotoxicity of Fe3O4@PDA-PEG-cRGD/BU NPs was analyzed using a cell counting kit-8 assay, Calcein-AM/PI double staining, and flow cytometry in HCT116 cells. The magnetic resonance imaging (MRI) performance and anti-tumor therapeutic efficacy of Fe3O4@PDA-PEG-cRGD/BU NPs were evaluated in HCT116-tumor bearing mice.Results: Fe3O4@PDA-PEG-cRGD/BU NPs had an average diameter of 260.4± 3.5 nm, the zeta potential of – 23.8± 1.6 mV, the drug loading rate of 1.1%, which had good thermal stability, photothermal conversion efficiencies and MRI performance. In addition, the released BU not only killed tumor cells but also interfered with glycolysis by targeting the steroid receptor coactivator 3 (SRC-3)/HIF-1α pathway, preventing intracellular ATP synthesis, and combating HSP-dependent tumor thermoresistance, ultimately strengthening the thermal sensitivity toward mild PTT both in vitro and in vivo.Conclusion: This study provides a highly effective strategy for enhancing the therapeutic effects of mild PTT toward tumors. Keywords: mild photothermal therapy, glycolysis metabolism, bufalin, HIF-1α, SRC-3